2018
DOI: 10.11613/bm.2018.030713
|View full text |Cite
|
Sign up to set email alerts
|

Significance of LDL and HDL subclasses characterization in the assessment of risk for colorectal cancer development

Abstract: IntroductionDyslipidaemia contributes to the occurrence of colorectal cancer (CRC). We hypothesized that qualitative changes of lipoproteins are associated with the risk for CRC development. This study analyses low-density lipoprotein (LDL) and high-density lipoprotein (HDL) diameters, as well as distribution of LDL and HDL subclasses in patients with CRC, with an aim to determine whether advanced lipid testing might be useful in predicting the risk for the onset of this malignancy.Materials and methodsThis ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…Although significant discrepancy among human and mouse resistin prevents deriving definitive conclusions, these findings suggest that elevation of circulating resistin levels in humans might arise as a consequence of decreased HDL-C and impaired HDL particle functionality. In our previous study, we demonstrated that HDL particle distribution in patients with CRC is characterized by lower diameter and increased proportion of smaller HDL3b particles, implying compromised HDL functionality [13]. Accordingly, in the current study, we found a change in PON-1 activity across tertiles of HDL-C (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Although significant discrepancy among human and mouse resistin prevents deriving definitive conclusions, these findings suggest that elevation of circulating resistin levels in humans might arise as a consequence of decreased HDL-C and impaired HDL particle functionality. In our previous study, we demonstrated that HDL particle distribution in patients with CRC is characterized by lower diameter and increased proportion of smaller HDL3b particles, implying compromised HDL functionality [13]. Accordingly, in the current study, we found a change in PON-1 activity across tertiles of HDL-C (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…This research was designed as a part of a larger project that investigated interactive role of dyslipidemia, oxidative stress, and inflammation in CRC, enrolling 126 patients as previously reported [12,13]. Patients were recruited from the Clinic of General Surgery, Military Medical Academy in Belgrade from July 2014 to January 2016.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…112 Additionally, we demonstrated in CRC patients that the distribution of HDL particles was shifted toward smaller and less functional HDL 3b particles. 113 Such inefficient maturation could have arisen as a consequence of lower activity of LCAT and higher CETP activity, resulting in the generation of smaller HDL particles enriched in triglycerides. 112 In addition, due to inefficient PON1 activity, a lack of protective effects against oxidative modification of HDL and LDL particles was likely.…”
Section: Pon1 and Carcinogenesismentioning
confidence: 99%
“…Apolipoprotein A‐I (ApoA‐I), the predominant protein in HDL‐C, has also been observed to be positively related to survival. In CRC patients, the level of HDL‐C was significantly lower compared to that in the health controls . CRC patients with metastases had substantially higher levels of low‐density lipoprotein cholesterol (LDL‐C) and LDL‐C to HDL‐C ratio than early‐stage patients .…”
Section: Introductionmentioning
confidence: 99%